Librarians’ Readiness for Artificial Intelligence Integration in Nigerian Academic Libraries: A Review of Literature - Jatto Esther Oluwayemi; Tella Adeyinka (Bìblìotečnij vìsnik, 2024)

(untitled)
The purpose of the article is to provide information professionals, including librarians, with a better understanding of the concepts and potential applications of artificial intelligence (AI) in library services. Scientific novelty. The article provides an overview of the literature on the readiness to implement artificial intelligence in library practice. It will go over the components of the Theory of Planned Behavior (TPB) model in connection with the management of library service delivery through AI tools. Lastly, a position on the preparedness of librarians for AI integration in university libraries will be adopted. Conclusions. The integration of artificial intelligence in Nigerian academic libraries is gaining momentum which has the potential to completely change how libraries function and provide services to their patrons. However, the readiness of librarians is crucial for successful implementation. This paper undertakes a review of the literature on how academic libraries in Nigeria are currently integrating AI and their readiness to use these tools. The results show that academic libraries in Nigeria are aware of the potential benefits of AI, but challenges like funding, infrastructure, and lack of expertise exist. To effectively use AI tools, librarians need to acquire new competencies and skills. Finally, the review offers suggestions for enhancing librarian readiness to fully exploit the potential of AI. In the Nigerian context, there is a notable scarcity of literature that has explored Librarians’ readiness to the adoption of artificial intelligence in an academic library: a literature review analysis of the current scope and necessary skills and competencies needed through qualitative research. As such, this study stands as a significant contribution to expanding our understanding of the topic.